The 21st Century Skills of School Administrators According to the Teachers’ Opinions in Piyamit Cluster Under the Secondary Educational Service Area Office Pathum Thani - Witchayapanyakul, Wit (Legal State Journal, 2023)
This research article aims to study the levels of the 21st century skills of school administrators according to the teachers’ opinions in Piyamit Cluster under the Secondary Educational Service Area Office Pathum Thani and to compare of the levels of the 21st century skills of school administrators according to the teachers’ opinions in Piyamit Cluster under the Secondary Educational Service Area Office Pathum Thani, based on education levels, positions and school sizes. The samples used in the research were 217 teachers. The instrument used to collect the data was a 5-point rating scale questionnaire with the discrimination values between 0.80-1.00, and the reliability value of 0.988. The statistics used in the data analysis were frequency distribution, percentage, mean, standard deviation, t-test, One-Way ANOVA and Scheffe’s comparison test. Findings are as follows: (1) The levels of the 21st century skills of school administrators according to the teachers’ opinions in Piyamit Cluster under the Secondary Educational Service Area Office Pathum Thani, in overall and each aspect were at a high level. (2) Teachers with different educational levels and positions had no significant different opinions on the 21st century skills of school administrators in Piyamit Cluster under the Secondary Educational Service Area Office Pathum Thani, both by overall and each aspect. (3) Teachers from different school sizes had different opinions on the 21st century skills of school administrators in Piyamit Cluster under the Secondary Educational Service Area Office Pathum Thani, by overall and each aspect at the statistically significant level of .05.